CHARACTERIZATION OF THE ZOOPLANKTON COMMUNITY STRUCTURE OF POLLUTED ERUVBI STREAM, BENIN CITY, NIGERIA - IMOOBE, T. O. T. (Nigerian Journal of Fisheries, 2011)
The zooplankton community of a polluted section of Eruvbi stream was analyzed emphasizing composition and abundance of organisms. Samples were collected monthly between March and August, 2009 from three stations in the system: upstream, discharge point, and downstream. Margalef’s species richness index (D), Shannon-Weiner index of general diversity (H’) and Evenness index (E) measures of diversity were used to describe the zooplankton community. Forty species made up of nine species of cladocerans, nine species of copepods and their developing stages and 22 species of rotifers were encountered during the study period with rotifers being the dominant taxa at all stations. The species richness of the zooplankton communities, at the polluted station 2 (discharge point) was however less than what obtained at the upstream and downstream stations. The most frequent zooplankton species in the polluted part of the stream were the rotifers Brachionus calyciflorus, Brachionus falcatus, Brachionus caudatus, and Testudinella patina. Regarding relative abundance, there was a common trend where rotifers were dominant in the three sampling stations, followed by copepods and cladocerans. All of these zooplankton groups showed lowest abundance in station 2 (discharge point).